Long-period earthquake ground displacements recorded on Guadeloupe (French Antilles). - Jousset, P.
Displacement time-histories derived from accelerograms of three recent earthquakes in western North America (Hector Mine, Mw 7.1; Denali, Mw 7.9; and San Simeon, Mw 6.5) have been shown to feature large long-period (∼10 s) ground-motion cycles. Such long-period displacements cause a localized peak within the displacement response spectrum that is currently not considered within any earthquake engineering design spectra. These displacement pulses have also been shown to be persistent and to feature on time-histories from widely separated stations (∼20 km). Broadband and accelerometric data from the Les Saintes earthquake sequence of 2004?2006 (4.9⩽Mw⩽5.3) recorded on Guadeloupe (French Antilles) are shown in this article to feature similar long-period motions. The broadband data are used to independently corroborate the displacement time-histories derived through high-pass filtering and double integration of accelerometric data. It is shown that high-quality broadband data are suitable for this purpose. The long-period motions observed cause a localized peak in displacement response spectra at periods between 5 and 10 s. It is suggested here that the cause of these large-amplitude long-period motions are specific source mechanisms, which may possibly involve the presence of fluids within the source. The form of the displacement response spectra from these time-histories is significantly different from the spectral shape specified in recent seismic design codes since the peak in the spectra is at a much greater period than expected. This leads to an underestimation of spectral displacements for periods between about 5 and 10 s. Therefore, if these observed long-period cycles are a common feature of earthquake ground motions the standard form of displacement design spectra may need to be reconsidered.
Keywords: Strong-motion data; Ground displacements; Displacement spectra; French Antilles; Source fluids